A survey on the development status of health examination (management) institution in Sichuan province in 2019 - CAO Min; SHI Qingke; LI Qianyao; WANG Zeng (Yixue xinzhi zazhi)
Objective To understand the development status of health examination (management) institutions in Sichuan province in 2019.Methods A questionnaire survey was used to obtain the basic information, human resources, health management service development and operation of health examination (management) institutions in Sichuan province in 2019.Results In 2019, among the 244 included health examination (management) institutions in Sichuan province, there were 123 tertiary hospitals, 97 secondary hospitals and 24 ungraded hospitals. 81.97% were public medical institutions; 16.80% of the institutions have been established for more than 15 years; 40.98% of the institutional medical examination business premises were 1 000~4 999m2. The number of basic diagnosis and treatment subjects in 6 institutions was less than 8. In 39.34% of institutions, the number of physical examination equipment was between 16 and 30. There were significant differences in the median number of primary and intermediate doctors, the median number of primary technicians and the median number of primary and intermediate nurses in different levels of institutions (P